Developmental changes in the neural responses to own and unfamiliar mother's smiling face throughout puberty - Takamura, Tsunehiko; Nishitani, Shota; Suegami, Takashi; Doi, Hirokazu; Kakeyama, Masaki; Shinohara, Kazuyuki (Frontiers in Neuroscience, 2015)
An attachment relationship between boys and their mother is important for subsequent development of the ability to sustain peer relationships. Affective responses to attachment figure, especially mother, is supposed to change drastically during puberty. To elucidate the neural correlates underlying this behavioral change, we compared the neural response of boys at three different developmental stages throughout puberty to visual image of their own mothers. Subjects included 27 pre-puberty boys (9.0 ± 0.6 years), 31 middle puberty boys (13.5 ± 1.2 years), and 27 post-puberty boys (20.8 ± 1.9 years), and their mother’s smile was video recorded. We measured their neural response in the anterior part of the prefrontal cortex (APFC) to their own mother’s smile compared with an unfamiliar-mother’s. We found that in response to their own mother’s smiling, the right inferior and medial part of the APFC (Ch6) was activated in the pre-puberty group. By contrast, the left inferior and medial (Ch4) and superior (Ch2 and Ch5) APFC were activated in the middle-puberty group, which is presumably linked to empathic feelings fostered by memories of mutual experience with own mother. These findings suggest that different patterns of APFC activation are associated with qualitative changes in affective response to own mother around puberty.